Optimizing biobased thermoset resins by incorporating cinnamon derivative into acrylated epoxidized soybean oil - Diego Lascano; Jaume Gomez-Caturla; David Garcia-Sanoguera; Daniel Garcia-Garcia; Juan Ivorra-Martinez (Materials & Design, 2024)
The study successfully developed thermoset materials utilizing acrylate epoxidized soybean oil (AESO) and allyl cinnamate (ACIN) with tert-butyl peroxybenzoate (TBPB) as the initiator. Isothermal curing at temperatures between 110 °C to 140 °C of the developed formulations, showed that higher temperatures accelerated the conversion process. The higher curing temperature increased the degree of conversion, leading to obtain the best flexural strength for samples cured at 130 °C. However, samples cured at 120 °C exhibited better impact properties due to a lower degree of conversion, which allows for a more mobile reticular network. In addition, morphological observations confirmed these mechanical property trends. Dynamic thermal characterization revealed changes in glass transition temperature and exothermic reactions due to unreacted products appeared for materials cured at low temperature. Increasing curing temperature allowed to enhance thermal stability by increasing molecular weight. Finally, thermomechanical analysis confirmed stiffness and glass transition temperature increases observed during flexural tests and thermal characterization.